Proceedings of the 13th ACM Workshop on Hot Topics in Networks 2014
DOI: 10.1145/2670518.2673882
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Load Imbalance in Real-World Networked Caches

Abstract: Modern Web services rely extensively upon a tier of in-memory caches to reduce request latencies and alleviate load on backend servers. Within a given cache, items are typically partitioned across cache servers via consistent hashing, with the goal of balancing the number of items maintained by each cache server. Effects of consistent hashing vary by associated hashing function and partitioning ratio. Most real-world workloads are also skewed, with some items significantly more popular than others. Inefficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 11 publications
1
59
0
Order By: Relevance
“…Service providers are well aware of the problems arising from skew-induced load imbalance [3,6]: servers that hold the most popular micro-shards can quickly become overwhelmed with user requests, degrading the whole system's performance and service quality. Data replication is a widely-used technique for dealing with such load imbalance in the datacenter.…”
Section: Dynamic Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Service providers are well aware of the problems arising from skew-induced load imbalance [3,6]: servers that hold the most popular micro-shards can quickly become overwhelmed with user requests, degrading the whole system's performance and service quality. Data replication is a widely-used technique for dealing with such load imbalance in the datacenter.…”
Section: Dynamic Replicationmentioning
confidence: 99%
“…The hottest micro-shard alone accounts for 4.2% of the total traffic, which is 20× the average load of an entire server in a 512-node cluster, and 85× in a 2048-node cluster of the same aggregate capacity. For a read-only workload, one solution is to combine aggressive replication across the cluster with caching at the application tier [5,6]. Unfortunately, neither replication nor caching is free for read-write workloads, as each copy needs to be updated on each write, regardless of the consistency model.…”
Section: Dynamic Replicationmentioning
confidence: 99%
“…In such a setting, skewed distributions emerge naturally, as data popularity varies greatly. Previous work has shown that data popularity distributions in real-world KVS workloads follow a power-law distribution [9,11,27,32], resulting in an access frequency imbalance, commonly referred to as skew. This skewed distribution is accurately represented by the powerlaw Zipfian distribution [9,15,17,27,37,55].…”
Section: Skew In Scale-out Architecturesmentioning
confidence: 99%
“…Service providers are well aware of the problems that arise from skew-induced load imbalance [20,21,32]: servers holding the most popular micro-shards can quickly become overwhelmed with user requests, degrading the whole system's performance and service quality. Data replication is a widely used technique that deals with such load imbalance in the datacenter.…”
Section: Replication: a Thorny Solutionmentioning
confidence: 99%
See 1 more Smart Citation